Anterior cruciate ligament reconstruction in a patient who has received systemic steroids for autoimmune disease - Tetsuro Ushio; Ken Okazaki; Hideki Mizu-uchi; Satoshi Hamai; Yukio Akasaki; Yasuharu Nakashima (Elsevier, 2018)
Background: An anterior cruciate ligament (ACL) reconstruction has become more common and the surgical morbidity has decreased, it has been performed not only in younger people to play sports but also middle-aged people, with satisfactory results. Therefore, some patients might have comorbidities for which they take medicines. Especially the medicines, such as systemic steroids, might influence the reconstructed ligament strength and durability. Case report: A 49-year-old woman who was taking oral steroids for autoimmune hepatitis suffered a spontaneous ACL injury. She complained of unstable symptoms in the knee despite initial conservative treatment. Then, she was treated operatively with autologous hamstring tendon grafts. Three years postoperatively, her knee remained stable with 1.8 mm side-to-side difference on a Kneelax arthrometer and with 1.6 mm on anterior stress radiographs. There was no rerupture or instability. Conclusion: The patient who had received systemic steroids for a long time recovered satisfactorily after the operation, with achievement of knee stability and possibility to prevent degenerative change in the knee joint. ACL reconstruction should be considered even in patients with such medication.